An investigation into the effects of hydro gymnastics on the quality of life, strength of limbs and the flexibility of elderly women: a study on the Chamber of Commerce Social Services - Fortaleza - Aguiar, Jaina Bezerra de; Gurgel, Luilma Albuquerque (Brazilian journal of physical education and sport, 2009)
This study was carried out at the Chamber of Commerce Social Services in the city of Fortaleza, CE, Brazil. Its aim was to test the effects of hydro gymnastics on elderly women general flexibility, limb strength and overall quality of life. Two groups consisting of thirteen women aged between sixty and eighty were evaluated. One group was a sedentary group and the other group had actively participated in hydro gymnastics for a minimum of six months. This research was used for"The Assessment on the Quality of Life" report proposed by the World Health Organization. Two tests were carried out within this study. The vertical jump test, as an indirect evaluation of muscular strength, and the sit-and-reach test evaluated flexibility. The findings were as follows: The hydro gymnastics group presented a higher score for the quality of life physical domain (4.5 ± 0.4 a.u.) significantly (p < 0.05) than the sedentary group (3.8 ± 0.7 a.u.), and for vertical jumping height (13.8 ± 3.7 cm and 10.5 ± 2.7 cm, respectively; p < 0.05) and flexibility test (41.3 ± 9.2 cm and 32.7 ± 4.6 cm, respectively; p < 0.05). The results of our study showed that elderly women, who regularly undertook hydro gymnastics, benefited from this form of exercise. Hydro gymnastics improved their strength, flexibility and their overall quality of life.